Edukasi & Pengenalan Absensi Digital Berbasis RFID di MI Mabniyatul Ihsan - Lailatus Sa'adah; Wisnu Mahendri; Fahmi Abdulloh Efendi; Toriq Andana Teguh Febriansyah; Abi Muhammad Wahid; Rohmatulloh Rohmatulloh (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This community service program was carried out through KKN-PPM at MI Mabniyatul Ihsan, Mojokerto, focusing on the introduction of digital attendance technology to elementary school students. The issue addressed in this program was the limited digital literacy among students and the lack of knowledge regarding digital attendance systems in schools. The purpose of the program was to improve students’ understanding of digital technology and provide practical experience in using an attendance system. The method applied included interactive lectures, demonstration of a prototype device, hands-on practice, and evaluation through pretest and posttest. The results indicated an increase in students’ comprehension of the concept of digital attendance technology, with the average score rising from 35.16% in the pretest to 45.18% in the posttest. This activity not only enhanced students’ knowledge but also stimulated their interest in technology and provided teachers with insights into the potential application of digital attendance for school administration.